Beta-blocker could show the prognostic impact in heart failure patients even on the regular hemodialysis. (14th October 2021) - Kishihara, M; Kentaro, J; Takuma, T; Takuro, A; Shota, S; Ayano, Y; Shonosuke, W; Yuichiro, M; Nobuhisa, H
Abstract: Background: β-blockers are recommended as standard medications for patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF). However, this favorable prognostic effect of β-blockers has not been fully validated in patients receiving regular hemodialysis. Indeed, prior clinical trials have generally excluded such very high-risk population for adverse cardiovascular events. Main reasons for that are the limited number of regular hemodialysis patients in the Western nations, and too high rates of clinical events. Purpose: This study aimed to clarify the prognostic benefit of β-blocker in patients on regular hemodialysis who were hospitalized due to HF. Methods: This observational study included 1, 930 consecutive patients who were hospitalized for worsening of HF and discharged alive from 2013 to 2019. Of them, 151 patients who underwent regular hemodialysis were ultimately analyzed. They were divided into 2 groups depending on the prescription of β-blocker at the discharge; β-blocker group (n=115) and No-β-blocker group (n=36). The primary endpoint of this study was a composite of death from any cause and rehospitalization due to HF. Results: During the observation period with 501 days of median follow-up (IQR: 197–954 days), the primary endpoint was occurred in 45 patients (39%) who were receiving β-blockers, while in 24 patients (67%) who were not. Kaplan-Meier analysis showed a significantly lower rate of the primary endpoint in patients in the β-blocker group (Log-rank, p<0.001, Figure). After the adjustment for age, sex, LVEF, systolic blood pressure, heart rate and atrial fibrillation, the administration of β-blocker was still an independent predictor for the primary endpoint in patients who underwent regular hemodialysis (hazard ratio; 0.46, 95% confidence interval; 0.26–0.82). Further analysis each for the population with reduced LVEF (<45%) and preserved LVEF (>45%) showed that the main result of the current study was consistent with that in the reduced LVEF group (Log-rank, p=0.005), but was diminished in the preserved LVEF group (p=0.13). Conclusion: The prescription of β-blocker at discharge in HF patients with regular hemodialysis was associated with lower risk of adverse cardiovascular events, mainly in the patients with reduced LVEF. From the findings of our study, we should consider the administration of β-blockers in HF patients, even they are on the regular hemodialysis. Funding Acknowledgement: Type of funding sources: None.